(3JbfjGJ GdeMGSHI GdeYebI habG ddOdjd GdeMGSHj GdhWfj GdLRA GdKGfj (B/s - (3ghGe, LeYIs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2002)
(3CYeGd fgGjI GdOhQI GdeMGSHjI(B- (3GdCfXeI GdeMGSHjI hELQGAGJ GdJSLjd GdeMGSHj(B- (3eMGhdI dEYGOI Jbjje YfGUQ GdCUhd hGdNUhe(B.s
Keywords: (3GdOdjd GdeMGSHjs; (3GdeMGSHIs; (3GdeMGSHI GdeYebIs